Improvement of sleep and melatonin in children with autism spectrum disorder after β‐1, 3/1, 6‐glucan consumption: An open‐label prospective pilot clinical study. Issue 9 (22nd August 2022) - Raghavan, Kadalraja; Dedeepiya, Vidyasagar Devaprasad; Kandaswamy, Ramesh Shankar; Balamurugan, Mangaleswaran; Ikewaki, Nobunao; Sonoda, Tohru; Kurosawa, Gene; Iwasaki, Masaru; Preethy, Senthilkumar; Abraham, Samuel JK
Abstract: Introduction: Poor sleep quality is a major problem in patients with autism spectrum disorder (ASD), and is attributed to low melatonin levels. Melatonin supplementation is recommended; however, its effectiveness varies. β‐Glucans have previously been shown to improve melatonin levels in animal studies. Herein, we examined the effectiveness of Aureobasidium pullulans (Nichi Glucan), a species of black yeast that contains beta‐1, 3/1, 6‐glucan, in a pilot study of children with ASD. Methods: Thirteen children (age, 2.5–13 years) with ASD were recruited for the study. The control group consisted of four patients (Gr. 1), while nine patients were classified into the treatment group (Gr. 2). Gr. 2 received 1 g of Nichi Glucan along with conventional therapy, whereas the Gr. 1 (control) patients received conventional therapy alone for 90 days. Serum melatonin levels and sleep patterns, assessed using a subjective questionnaire, were evaluated before and after treatment. Results: In Gr. 2, the average serum melatonin level increased from 238.85 ng/L preintervention to 394.72 ng/L postintervention. Eight of nine participants (88%) in Gr. 2 showed improvements in sleep pattern and quality, while no improvement was observed in the participants in Gr. 1. Conclusion: The consumption of Nichi Glucan for 90 days resulted in visible improvement in sleep quality, sleep pattern, and serum melatonin levels, which was reported for the first time by our study. A larger multicenter study is required to validate our findings.